2014
DOI: 10.1038/srep03961
|View full text |Cite
|
Sign up to set email alerts
|

Near Field Enhanced Photocurrent Generation in P-type Dye-Sensitized Solar Cells

Abstract: Over the past few decades, the field of p-type dye-sensitized solar cell (p-DSSC) devices has undergone tremendous advances, in which Cu-based delafossite nanocrystal is of prime interest. This paper presents an augment of about 87% improvement in photocurrent observed in a particular configuration of organic dye P1 sensitized CuCrO2 delafossite nanocrystal electrode coupled with organic redox shuttle, 1-methy-1H- tetrazole-5-thiolate and its disulfide dimer when Au nanoparticles (NPs, with diameter of about 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…The most attractive features of delafossite oxides should rest with their high p-type conductivity and optical transparency, which have been firstly discovered in CuAlO 2 by Hisono et al and well explained by the ''chemical modulation of valance band'' theory [4]. Recently, several groups including ours started the applications of delafossite oxides nanocrystalline as the photocathode materials in p-type dye-sensitized solar cells (DSSCs), in replacement of conventional NiO, and several successful examples include CuAlO 2 [5,6], CuGaO 2 [7][8][9][10] and CuCrO 2 [11][12][13][14]. As reflected in all of the previous works [10][11][12][13][14], size control of the delafossite nanocrystals are critical for the high performance of p-type DSSCs [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…The most attractive features of delafossite oxides should rest with their high p-type conductivity and optical transparency, which have been firstly discovered in CuAlO 2 by Hisono et al and well explained by the ''chemical modulation of valance band'' theory [4]. Recently, several groups including ours started the applications of delafossite oxides nanocrystalline as the photocathode materials in p-type dye-sensitized solar cells (DSSCs), in replacement of conventional NiO, and several successful examples include CuAlO 2 [5,6], CuGaO 2 [7][8][9][10] and CuCrO 2 [11][12][13][14]. As reflected in all of the previous works [10][11][12][13][14], size control of the delafossite nanocrystals are critical for the high performance of p-type DSSCs [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…This observation was explained by a triggered interfacial charge recombination between the metallic nanoparticles and their neighbor mediators 42. Previous investigation on dye‐sensitized solar cells revealed that the augmented photocurrent could be contributed both from the scatter effect of metallic nanoparticles and/or the boosted charge separation efficiency when gold NRs was used 42. As shown in Table 1, there is about 3.5 mA cm −2 enhancement in the J SC for device C compared with device A.…”
Section: Resultsmentioning
confidence: 90%
“…The photovoltaic performances of these devices have been published in our previous reports. 16,24,25 The CuCrO 2 -based p-type DSSC with P1 dye in combination with iodide-based electrolyte presented a PCE of about 0.05%, which was higher than that of device using the C343 as sensitizer (being about 0.019%). The e±ciency was promoted to about 0.17% by using the transparent organic electrolyte of T À and its dimmer T 2 .…”
Section: Resultsmentioning
confidence: 99%